Macrophage phagocytosis cracking the defect code in COPD - Jubrail, Jamil (Biomed J, 2017)
In the normal non-diseased lung, various macrophage populations maintain homeostasis and sterility by ingesting and clearing inhaled particulates, pathogens and apoptotic cells from the local environment. This process of phagocytosis leads to the degradation of the internalized material, coordinated induction of gene expression, antigen presentation and cytokine production, implicating phagocytosis as a central regulator of innate immunity. Phagocytosis is extremely efficient and any perturbation of this function is deleterious. In inflammatory lung diseases such as chronic obstructive pulmonary disease (COPD), despite their increased numbers, macrophages demonstrate significantly reduced phagocytic capacity of bacteria and apoptotic cells. This defect could play a role in dysbiosis of the lung microbiome contributing to disease pathophysiology. In this review, we will discuss lung macrophages, describe phagocytosis and its related downstream processes and the reported phagocytosis defects in COPD. Finally, we will briefly examine current strategies that focus on restoring the phagocytic capabilities of lung macrophages that may have utility in COPD.